ANALISIS INTERAKSI PADATAN PIPERIN DENGAN BEBERAPA ASAM DIKARBOKSILAT - Farah Fauziah, Alya
Piperine is the secondary metabolite from the piperidine alkaloid group in black pepper (Piper nigrum L.) with extremely low solubility in water. Multicomponent crystals formation is one way of improving the solubility and dissolution rate of piperine. In this research, we will form the multicomponent crystals of piperine (PIP) with dihydrate oxalic acid (OKS), azelaic acid (AZE), and maleic acid (MAL) in molar ratio each of 1:1, the preferred method is solvent evaporation with methanol. The multicomponent crystal formation begins with creating the binary phase diagram to observe the probability of solid interactions as well as determining the appropriate molar ratio. The obtained crystals were then characterized by electrothermal, DSC, FTIR, and PXRD instruments. The melting points of PIP-OKS, PIP-AZE, and PIP-MAL are 65,6-125 °C, 76-123,9 °C, and 60,8-129,5 °C, respectively. The FTIR spectrum of PIP-OKS, PIP-AZE, and PIP-MAL showed a similar pattern and on each spectrum, novel peaks were observed at wavenumber 3467 cm -1 . The diffractograms of PIP- OKS, PIP-AZE, and PIP-MAL were different from it physical mixture, however, the three crystals showed similar diffraction peaks, which were at 2?= 4,8°, 13,4°, 19,2°, 21,5°, 23,4°, 27,2°, and 29,2°. The DSC analysis for the PIP-OKS crystal and PIP-AZE crystal showed endothermic peak at 94 °C and 99,6 °C. From this research, it can be inferred that a novel crystal phase has formed due to the interaction of piperine with dihydrate oxalic acid, azelaic acid, and maleic acid, which exhibited similar crystal structure or known as isomorph.